New records of the genus Hansenomysis in Japan with descriptions of a new species (Crustacea: Mysidacea: Petalophthalmidae) - Bravo, M. R.; Murano, M. (Proceedings of the Biological Society of Washington, 1997)
M1202
NeMys doc_id: 3527